The relationship between core job dimensions and employees job performance at Malaysia Building Society Berhad (MBSB), Melaka. / Mohamad Qamarul Hazeq Mohamad Ridza - Mohamad Ridza, Mohamad Qamarul Hazeq (Faculty of Business and Management, 2014)
The success of an organization depends on the people who work within the organization. Job performance can be defined as the accomplishment of work-related tasks or skills by an employee or trainee that may refer to specific skills or to overall performance (Hackman and Oldham, 1974). Therefore, it is also used for factors associated with success or failure in job situations and most refers to whether an employee performs their job well. On the other definition, job performance is defined in terms of rise in the level of output of services with the same or reduced level of input as a result of better work methods and improved technology (Sharma, 2007). It means that, employee's performance is more important than equipment and raw material. There are two factors that include under the job performance. First is the task performance where it is a traditional method on doing something like to transform and maintain the raw material to ensure the organizational operation. The contextual performance is about the interpersonal and behavior that supports social interaction within the organization. The successful of the job performance is based on the five core job dimensions which include the autonomy, feedback, skill variety, task significance and task identity. All of the core job dimension will be determine whether or not the employee will be internally motivated to work effectively.Hence,this study focuses on identifying the relationship between core job dimensions and the employees job performance in Malaysia Building Society Berhad (MBSB) Melaka.